PEEK versus Metallic Attachment-Retained Obturators for Patient Satisfaction: A Randomized Controlled Trial - Sharaf, Mohamed Yahia; Eskander, Asharaf Email (European Journal of Dentistry, 2021)
Objective The aim of the study was patients’ satisfaction evaluation and radiographic evaluation of the terminal abutments of attachment-retained maxillary obturators with metal framework versus milled polyetheretherketone (PEEK) framework in the management of maxillectomy cases.Materials and Methods Eighteen participants were randomly divided into three parallel groups (n = 6). Participants of the PEEK group received attachment-retained obturators with milled PEEK framework, the metal group received an attachment-retained obturator with a metallic framework, and the conventional group received conventional clasp-retained obturators with a metallic framework (Control group). The evaluation included was radiographic evaluation and patients’ satisfaction in this study included two scales—”The Obturator Functioning Scale” and “The European Organization for Research and Treatment of Cancer Head and Neck 35” using one-way ANOVA test.Results Both PEEK and metal groups showed a statistically significant lower mean bone loss (p <0.050) compared with the conventional group during all follow-up periods. There is no statistically significant difference between the PEEK and metal groups during all follow-up periods. Regarding patient satisfaction, both the PEEK and metal groups showed a statistically significant decrease score (p <0.050) compared with the conventional group in various aspects of patients’ satisfaction scales as satisfaction with the look and difficulty of talking to the public, and noticeable clasps. In comparison, the PEEK group showed a statistically significant decrease score (p <0.050) than the metal group with respect to satisfaction with the look along all follow-up periods.Conclusions PEEK attachment-retained maxillary definitive obturators could be considered a promising treatment modality for patients with acquired maxillary defects with regard to esthetics and satisfaction.
Keywords: attachment; maxillectomy; obturator; patient satisfaction; PEEK